Alcohol Excites Cerebellar Golgi Cells by Inhibiting the Na(+)/K(+) ATPase - Botta, Paolo (Nature Publishing Group, 2010)
Alcohol-induced alterations of cerebellar function cause motor coordination impairments that are responsible for millions of injuries and deaths worldwide. Cognitive deficits associated with alcoholism are also a consequence of cerebellar dysfunction. The mechanisms responsible for these effects of ethanol are poorly understood. Recent studies have identified neurons in the input layer of the cerebellar cortex as important ethanol targets. In this layer, granule cells (GrCs) receive the majority of sensory inputs to the cerebellum through the mossy fibers. Information flow at these neurons is gated by a specialized pacemaker interneuron known as the Golgi cell, which provides divergent GABAergic input to thousands of GrCs. In vivo electrophysiological experiments have previously shown that acute ethanol exposure abolishes GrC responsiveness to sensory inputs carried by mossy fibers. Slice electrophysiological studies suggest that ethanol causes this effect by potentiating GABAergic transmission at Golgi cell-to-GrC synapses through an increase in Golgi cell excitability. Using patch-clamp electrophysiological techniques in cerebellar slices and computer modeling, we show here that ethanol excites Golgi cells by inhibiting the Na(+)/K(+) ATPase. Voltage-clamp recordings of Na(+)/K(+) ATPase currents indicated that ethanol partially inhibits this pump and this effect could be mimicked by low concentrations of ouabain. Partial inhibition of Na(+)/K(+) ATPase function in a computer model of the Golgi cell reproduced these experimental findings. These results establish a novel mechanism of action of ethanol on neuronal excitability, which likely has a role in ethanol-induced cerebellar dysfunction and may also contribute to neuronal functional alterations in other brain regions.